Formulating Halal-Based Hospital Indicators - Aisyah As-Salafiyah (Halal Tourism and Pilgrimage, 2022)
This study aims to formulate the halal-based hospital indicators using systematic review. Research will be conducted in 2021 by searching with the keyword "Halal Hospital". The data analyzed 30 halal-based hospital research publications indexed by Dimensions. Visualization of the map of the development of halal-based hospital research is obtained through the export process into the .txt file format. The export data is then processed and analyzed using the VOSviewer application program to find a bibliometric map of the development of halal-based hospital research. The results show that the number of publications on halal-based hospital research is from 2014 to 2021. Bibliometric mapping shows that the visualization of the development of halal-based hospital research is divided into 5 clusters, with the most popular keywords being hospital, Islamic medical tourism and health care provider. The most popular writers are Suhaiza Zailani and Hayatullah Lalulddin. The most popular journal is IIUM Medical Journal Malaysia (IMJM) and the most popular document is Rahman et al. (2018b). In addition, this study found indicators that are the main elements of a halal-based hospital based on Maqashid Syariah and recommendations for related parties.